Review of recent advances in bone scaffold fabrication methods for tissue engineering for treating bone diseases and sport injuries - Zhou, Zeng; Feng, Wei; Moghadas, B. Kamyab; Baneshi, N.; Noshadi, B.; Baghaei, Sh.; Dehkordi, D. Abasi (Churchill Livingstone, 2024)
Despite advancements in medical care, the management of bone injuries remains one of the most significant challenges in the fields of medicine and sports medicine globally. Bone tissue damage is often associated with aging, reduced quality of life, and various conditions such as trauma, cancer, and infection. While bone tissue possesses the natural capacity for self-repair and regeneration, severe damage may render conventional treatments ineffective, and bone grafting may be limited due to secondary surgical procedures and potential disease transmission. In such cases, bone tissue engineering has emerged as a viable approach, utilizing cells, scaffolds, and growth factors to repair damaged bone tissue. This research shows a comprehensive review of the current literature on the most important and effective methods and materials for improving the treatment of these injuries. Commonly employed cell types include osteogenic cells, embryonic stem cells, and mesenchymal cells, while scaffolds play a crucial role in bone tissue regeneration. To create an effective bone scaffold, a thorough understanding of bone structure, material selection, and examination of scaffold fabrication techniques from inception to the present day is necessary. By gaining insights into these three key components, the ability to design and construct appropriate bone scaffolds can be achieved. Bone tissue engineering scaffolds are evaluated based on factors such as strength, porosity, cell adhesion, biocompatibility, and biodegradability. This article examines the diverse categories of bone scaffolds, the materials and techniques used in their fabrication, as well as the associated merits and drawbacks of these approaches. Furthermore, the review explores the utilization of various scaffold types in bone tissue engineering applications.
Keywords: Medical treatment; Physical treatment; Porous Scaffolds; Orthopedic tissue; Biomedical applications